Distortionary agricultural trade policy and food security: a causal analysis - Mohamed, Shaheera; Khalid, Haniza (Pusat pengajian Ekonomi, Fakulti Ekonomi dan Pengurusan, Universiti Kebangsaan Malaysia (UKM), 2016)
In an increasingly globalised world, agricultural trade and food security inevitably goes hand in hand. On paper, the idea of free agricultural trade is appealing as it will lead to a larger access of quantity and variability of food to more people. In practice, many countries choose to protect their borders through distortionary agricultural trade policies in an attempt to keep domestic markets isolated from changes in international price. The food crisis of 2007-2008 led a to an increase in border protection for many countries, particularly in the agricultural sector. In the academic field, there is still a dispute on the impact that distortionary agricultural trade policies have on food security. Therefore, determining the causal relationship between distortionary agricultural trade policies and food security is an important element in establishing a foundation for academic discussion. This paper aims to analyse the causal impact that distortionary agricultural trade policies have on food security, utilising the generalised propensity score (GPS) method, a non-parametric matching technique with continuous treatment, to assess the effect that distortionary agricultural trade policies, proxied by the Nominal Rates of Assistance (NRA), has on the four dimensions of food security; food access, food availability, food utilisation and food stability. The data focuses on 24 developing countries in the Asian, African and Latin American region between the years of 1990 to 2010. The results of the research show that there is a degree of causal relationship between distortionary agricultural trade policies and the dimensions of food security. The results also found a positive relationship between distortionary agricultural trade policies and food security in developing countries.